Inclusion of bakery?s residues in some metabolites and bromatological indicators of the solid state fermentation of apple pomace - Castillo, Yamicela; Ruiz, O.; Angulo, C.; Rodr?guez, C.; El?as, Arabel; La O, Oreste (Cuban Journal of Agricultural Science, 2011)
The effect of the inclusion levels of bakery?s residues (BR) (0, 15, 30, and 45 %) with apple pomace (AP) on the bromatological indicators, the pH, and the count of yeasts was assessed through the utilization of solid state fermentation (SSF) at different times (0, 24, and 48 h), using completely randomized design in factorial fit (4x3) and six repetitions. The bakery?s residues were wastes of white bread, integral bread, and sweet bread. The pH increased, regardless the treatment, with the BR inclusion at values ranging from 4.07 to 5.44, and declined with the fermentation time in the four treatments (P ? 0.0008). The counts of yeasts expressed in log10 increased throughout the fermentation time in all the treatments (P ? 0.0001), with values ranging from 7.41 to 10.71 depending on the specific treatment, except the control, in which the 24 and 48 hours remained without differences. The treatments with 30 and 45 % of bakery?s residues (BR) increased significantly (P < 0.001) the counts of yeasts, compared with the control and the 15 % BR inclusion. The dry matter (DM) at the start of the fermentation (hour 0) rose (P ? 0.0001) as the BR levels increased (79.98, 84.86, 86.78, and 87.90 %, respectively), but fell significantly with the fermentation times at the hour 0, with increase at 24 h in the treatments of 15 and 30 %, but without significant differences at 48 h, compared with the start of the fermentation. The ether extract (EE) also increased significantly with the BR rise and with the fermentation hours, in the treatments with 15, 30, and 45 % of BR. The crude fiber (CF) decreased (P ? 0.0001) with the increasing level of BR. The crude protein (CP) decreased significantly, as the level of BR increased, with values that varied at 25.9 - 19.1, 27.0 - 22.9, and 28.6 - 21.6 for 0, 24, and 48 h, respectively. However, the true protein (TP) rose (P ? 0.0001), as the level of BR and the fermentation time increased in all the treatments. It was concluded that the inclusion of increasing levels of BR improved substantially the fermentative and bromatological indicators in the end products. Key words: fermentation, apple wastes, bakery?s residues, bromatology.